NELAYAN SELAT NASIK DAN ALTERNATIF PEMBERDAYAAN - Imron, Masyuri (Jurnal Masyarakat dan Budaya, 2006)
Selat Nasik is a district in Kabupaten Belitung. Most of the people living in this area are fishermen, who live in poverty. Among the causes of their poverty are simplicity of their fishing gear, and no market access. To develop fishing gear, fulfill their daily needs and operational cost for fishing, some of them borrow money from fish trader. However, this has created dependency, and on the consequence, their fishes are bought in a cheaper price. To empower fishermen in this area, many aspects should be attended. Firstly, institutional replaces of the role of fish traders. This institution is expected to help provides capital forfishermen, and in return the payment should be adapted with the fishermen fluctuative income. Secondly, to handle limited access to market, there is a need to build a TPI (place for fishing auction) in the area. The existence of TPI is expected to increase the price of fish, because only traders with highest bargains get fish from fishermen. Last but not least, participation of local people in deciding adequate empowerment programme is a necessity, keeping in mind that fishermen are subjects of empowerment, not as an object. Kata Kunci: Nelayan; kemiskinan; pemberdayaan